2013
DOI: 10.4049/jimmunol.1202042
|View full text |Cite
|
Sign up to set email alerts
|

A Novel IRAK1–IKKε Signaling Axis Limits the Activation of TAK1–IKKβ Downstream of TLR3

Abstract: IRAK1 is involved in the regulation of type I IFN production downstream of TLR3. Previous work indicated that IRAK1 negatively regulates TRIF-mediated activation of IRF3 and IRF7. We report that IRAK1 limits the activation of the TLR3–NF-κB pathway. Following TLR3 stimulation, IRAK1-deficient macrophages produced increased levels of IL-6 and IFN-β compared with wild type macrophages. Pharmacological inhibition of TAK1 reduced this increase in IFN-β, together with the heightened activation of IRF3 and p65 found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…MST1 directly bound to and phosphorylated IL-1 receptor-associated kinase 1 (IRAK1), leading to the degradation of IRAK1 (55). IRAK1 has been proven to negatively regulate MyD88-, TRIF-, and RIG-Imediated IFN-β production (56,57). Therefore MST1-mediated degradation of IRAK1 potentiated IRF3 activation and IFN-β production (55).…”
Section: Hippo-yap and Ifn-i Signalingmentioning
confidence: 99%
“…MST1 directly bound to and phosphorylated IL-1 receptor-associated kinase 1 (IRAK1), leading to the degradation of IRAK1 (55). IRAK1 has been proven to negatively regulate MyD88-, TRIF-, and RIG-Imediated IFN-β production (56,57). Therefore MST1-mediated degradation of IRAK1 potentiated IRF3 activation and IFN-β production (55).…”
Section: Hippo-yap and Ifn-i Signalingmentioning
confidence: 99%
“…The IKKi/IKKe-IRAK1 interaction downstream of TLR3 is described in ref. [239]. MD2, lymphocyte antigen 96; RAC1, Ras-related C3 botulinum toxin substrate 1; TAB, TAK1-binding protein.…”
Section: Positive Regulators Of Trif-dependent Tlr Signalingmentioning
confidence: 99%
“…(D and E) Relative ratio of phospho-STAT1/PCNA (nuclear loading control) in WT and IRAK1 2/2 BMDM at 1 and 3 h following poly(I:C) and LPS stimulation, as determined by densitometric analysis of three independent experiments. (35). In this study, we observed no increase in IRF3 activation in IRAK1 2/2 BMDM following TLR4 ligand stimulation (Supplemental Fig.…”
Section: Irak1 Regulates Irf1 and Irf9 Key Regulators Of Il-27p28 Exmentioning
confidence: 48%
“…MRT67307 inhibited TLR3/4-induced IFN-b expression in WT BMDM and in LPS-stimulated IRAK1 2/2 macrophages. In contrast, we detected high levels of IFN-b in poly(I:C)-stimulated IRAK1 2/2 compared with WT macrophages (35), which we found to remain high following MRT67307 treatment (Fig. 1D).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation